PENGEMBANGAN BUKU TEKS PADA MATERI PROSES MORFOLOGIS BAHASA INDONESIA BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) - Afif Rofii; Lisa Yuniarti; Uli Wahyuni (Universitas Batanghari, 2025)
The purpose of this research is to describe the development process of contextual-based learning textbook on the subject morphology process that is valid, practical, and effective. The type of the research is Research and Development/ R&D with 4-D research model that starts with defining step, designing, and then developing. This research uses quantitative approach. The data type of this research is quantitative data that consist of three types of data which are data validated by expert, data from practitioner’s assessments, and effectiveness data in form of learning results and student’s activities. Research result shows that contextual-based textbook on morphology that is being developed is valid, practical, and effective. This could be seen in the validity of the textbook with a score of 91,95 which falls into very valid criteria. The practicality of lecturer’s textbook is very practical with a score of 95 and the practicality of student’s textbook is 80,53 which fall into the criteria of very practical. The effectiveness of textbook, which consists of student’s learning results have average classical of 75,42 which is qualified as Good (B) and the activities of students got a score of 89,52 with classification very active.